2011
DOI: 10.4088/jcp.10r06531
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Antidepressants for Late-Life Depression

Abstract: The present meta-analysis suggests that antidepressants are efficacious in late-life MDD, but significant study heterogeneity suggests that other factors may contribute to these findings. A secondary analysis raises the possibility that efficacy of these agents may be reduced in trials involving patients aged 65 years or older. Why antidepressants may be less efficacious in elderly versus younger subjects remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(97 citation statements)
references
References 0 publications
1
90
1
3
Order By: Relevance
“…Neuroimaging markers may inform treatment by identifying depressed adults likely to remit with pharmacotherapy, an individualized therapeutic dose, and treatment response [29, 39]. In essence, treatment results in VaDep patients are still unsatisfying and, regardless of causal mechanisms, persons with depressive disorders and vascular disease represent a high-risk group for poor treatment response [214]. The prevalence of treatment-resistant LLD was estimated between 26 and 41 per 100 person years [215].…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging markers may inform treatment by identifying depressed adults likely to remit with pharmacotherapy, an individualized therapeutic dose, and treatment response [29, 39]. In essence, treatment results in VaDep patients are still unsatisfying and, regardless of causal mechanisms, persons with depressive disorders and vascular disease represent a high-risk group for poor treatment response [214]. The prevalence of treatment-resistant LLD was estimated between 26 and 41 per 100 person years [215].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 35.3% of the cases of late-life depression may be regarded as mild, 51.9% as moderate, and 12.7% as severe 5. Increasing age in depressed patients accounts for higher percentages of cases with unfavorable clinical course, with higher relapse rates,6 worse treatment response, and incomplete functional recovery 7,8. Furthermore, depression in the elderly is a highly under-recognized syndrome (40%–60% of cases) 9.…”
Section: Epidemiology Of Mood Disorders In Late Lifementioning
confidence: 99%
“…Although tricyclic ADs and selective serotonin reuptake inhibitors (SSRIs) are reported to be effective in clinical trials with older patients (Gareri et al, 2000; Salzman et al, 2002; Blazer, 2003) some authors have claimed that their effectiveness is reduced compared to that found in young adults (Lenze et al, 2008; Sheffrin et al, 2009; Tedeschini et al, 2011). Moreover, it has been suggested that such decline begins at middle age as a modest reduction that becomes more pronounced at senescence (Tedeschini et al, 2011). …”
Section: Introductionmentioning
confidence: 99%